Chippewa Indians making Birch Canoes. / Whitney & Zimmerman, Photographers, Saint Paul - Whitney & Zimmerman, photographer. (William L. Clements Library, 1870)
View of unidentified Ojibwa Indian men crafting birch canoes. A birch bark wigwam is present in background.; Title derived from image caption.; Printed on front left-hand margin: Lake Superior Scenery, South Shore.; Printed on front right-hand margin: Whitney & Zimmerman, Photographers, Saint Paul.; "Ojibwa Indians" variant names: Anishinaabe, Chippewa Indians, Ojibwe Indians.